Prevalence of Asymptomatic Bacteriuria during Pregnancy at a Tertiary Care Hospital of Province No. 2, Nepal (Tribhuvan University Journal of Microbiology, 2019)
Objectives: The objective of this study was to determine the prevalence of asymptomatic bacteriuria in pregnant women, identify the causative agent responsible for urinary tract infection (UTI) and its antibiotic susceptibility.Methods: The mid-stream urine sample was streaked on the MacConkey agar (MA) and Blood agar (BA) medium by the semi-quantitative culture technique. Identification of significant isolates was done by standard microbiological techniques. Antibiotic susceptibility test of the isolated organisms was done by modified Kirby Bauer disc diffusion method.Results: The prevalence rate of asymptomatic urinary tract infection (AUTI) among pregnant women was found to be 42%. The highest number of UTI cases found during pregnancy was in between age 21-25 years (52.22%), in second gravida (51.59%), during 3rd trimester of pregnancy (49.68%) and in winter with 52.22%. E. coli was principal organism to cause AUTI (35.48%) during pregnancy. Amikacin, imipenem and nalidixic acid were effective towards Gram negative bacilli whereas vancomycin, tetracycline and amoxyclav were effective towards Gram positive cocci.Conclusion: All pregnant women visited for antenatal checkups should be advised for the culture and sensitivity test of their urine specimens which will reduce the maternal and child health complications. Different screening test and awareness programme should be conducted at regular interval of time for prevention of AUTI during pregnancy.